Review: Prison Dancer: The Musical — a nod to the Filipino as a world-class talent - Rosales, Rey (My University, 2023)
Prison Dancer: The Musical has all the hallmarks of a hit musical: catchy tunes, perfectly executed choreography, and a storyline that captures the hearts of audiences, regardless of background. The show has the potential to equal or surpass the success of another all-Filipino cast musical, Here Lies Love, which premiered on Broadway in 2023.
Keywords: Review; Prison Dancer: The Musical